Karakteristik Bahasa Arab Pra-Islam: Analisis Masa Jahiliyyah - Andi Abdul Hamzah; Kamaluddin Abunawas; Ummu Fadhilah Imran Ibrahim (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2025)
This research investigates the significance of the Arabic language during the Jahiliyyah era in the formation of the social and cultural identity of the Arab community prior to the rise of Islam. The study centers on how language, especially through poetry, served as an instrument for asserting identity, power, and moral values. Utilizing a qualitative descriptive approach with content analysis, the research focuses on the works of renowned poets like Imru’ al-Qais and Antarah ibn Shaddad. Data collection was conducted through a comprehensive review of literature, analyzing diwan and other pertinent texts, while examining the interplay between language, social values, and the poets' influence within the political and social milieu of the time. The results demonstrate that in the Jahiliyyah period, language was not merely a communicative tool, but also a means to reinforce tribal identity and safeguard social honor. This study offers valuable insights into the role of language within social and political frameworks and can aid in the development of educational curricula for Arabic language and literature, particularly with regard to cultural and historical literacy. Furthermore, the research paves the way for further studies on the relationship between language and social transformation, particularly in the transition from the Jahiliyyah period to the Islamic period. Keywords: Jahiliyyah Arabic; Social and Cultural Identity; Poetry and Moral Expression Penelitian ini membahas peran bahasa Arab pada masa Jahiliyyah dalam membentuk identitas sosial dan budaya masyarakat Arab sebelum kedatangan Islam. Penekanan utama terletak pada bagaimana bahasa, khususnya dalam bentuk puisi, digunakan sebagai sarana untuk membangun identitas, kekuasaan, dan ekspresi moral. Metode yang diterapkan adalah pendekatan kualitatif deskriptif dengan content analysis, yang memfokuskan pada karya-karya penyair terkenal seperti Imru’ al-Qais dan Antarah ibn Shaddad. Pengumpulan data dilakukan melalui studi pustaka dengan menganalisis diwan serta literatur yang relevan, sambil menggali keterkaitan antara bahasa, nilai-nilai sosial, dan peran penyair dalam konteks politik dan sosial pada masa tersebut. Hasil penelitian menunjukkan bahwa pada masa Jahiliyyah, bahasa bukan hanya sekadar alat komunikasi, tetapi juga berfungsi untuk memperkuat identitas suku dan menjaga kehormatan sosial. Penelitian ini memberikan kontribusi penting dalam memahami peran bahasa dalam struktur sosial dan politik, serta dapat digunakan untuk1 mengembangkan kurikulum pendidikan bahasa Arab dan sastra, dengan fokus pada aspek budaya dan literasi sejarah. Selain itu, penelitian ini membuka peluang untuk penelitian lebih lanjut mengenai hubungan antara bahasa dan perubahan sosial, khususnya pada periode transisi dari Jahiliyyah ke Islam. Kata Kunci: Bahasa Arab Jahiliyyah; Identitas Sosial dan Budaya; Puisi dan Ekspresi Moral